2020
DOI: 10.1108/jarhe-11-2019-0286
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence and academic achievement in higher education

Abstract: PurposeThis study examines the role of emotional intelligence on academic achievement among students at a private university in Kuwait.Design/methodology/approachThe data were obtained through a questionnaire which elicits information on students' sociodemographic data and their overall college grade point average (GPA). The 16-item Wong and Law Emotional Intelligence Scale (WLEIS, Wong and Law, 2002), was used to evaluate the level of emotional intelligence and explore the effect on academic performance in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 76 publications
0
31
0
1
Order By: Relevance
“…Pedrosa et al ( 2020 ) observed the connection between emotional challenges with the perspectives of students; they found that the psychological stress and burnout of students become more obvious. Consequently, regulation, controlling, and managing feelings and emotions are deemed compulsory for successful academic performance (Suleman et al, 2019 ; Halimi et al, 2020 ; MacCann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pedrosa et al ( 2020 ) observed the connection between emotional challenges with the perspectives of students; they found that the psychological stress and burnout of students become more obvious. Consequently, regulation, controlling, and managing feelings and emotions are deemed compulsory for successful academic performance (Suleman et al, 2019 ; Halimi et al, 2020 ; MacCann et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This concept can be defined as the innate ability of an individual to take what they perceive, and understand and manipulate these perceptions from both their own emotions and those of others. The aim of this is to function in society in an intelligent and appropriate way [ 16 , 17 , 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This aspect also coincides with previous research [24] in which authors such as [143] highlighted nationality as one of the most influential factors in the development of social skills in immigrant students. According to [144], this may be due to the fact that the traditions, cultures and customs of each nationality determine the intercultural dialogue that takes place and, with it, the acquisition (or not) of certain social skills [39].…”
Section: Discussionmentioning
confidence: 99%